2013
DOI: 10.3109/03091902.2013.810788
|View full text |Cite
|
Sign up to set email alerts
|

The effect of foot arch on plantar pressure distribution during standing

Abstract: The aim of this study was to explore how foot type affects plantar pressure distribution during standing. In this study, 32 healthy subjects voluntarily participated and the subject feet were classified as: normal feet (n = 23), flat feet (n = 14) and high arch feet (n = 27) according to arch index (AI) values obtained from foot pressure intensity image analysis. Foot pressure intensity images were acquired by a pedopowergraph system to obtain a foot pressure distribution parameter-power ratio (PR) during stan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 41 publications
0
27
0
5
Order By: Relevance
“…A continuación, se observa un esquema de los datos más representativos de las presiones del pie cavo ( Fig. 2) y una imagen representativa de las presiones típicas de pie cavo ( En relación a las presiones plantares del pie cavo comparadas con el pie normal, existen varios estudios que muestran la diferencia (7,14,15).…”
Section: Presiones Plantares En El Pie Cavounclassified
See 1 more Smart Citation
“…A continuación, se observa un esquema de los datos más representativos de las presiones del pie cavo ( Fig. 2) y una imagen representativa de las presiones típicas de pie cavo ( En relación a las presiones plantares del pie cavo comparadas con el pie normal, existen varios estudios que muestran la diferencia (7,14,15).…”
Section: Presiones Plantares En El Pie Cavounclassified
“…En relación al pie cavo y al pie plano, hay estudios que comparan las presiones plantares de estas dos tipologías de pie entre sí, a parte de la comparativa mencionada anteriormente con el pie normal (15,18).…”
Section: Figura 4 Presiones Plantares Del Pie Planounclassified
“…Higher arch height is associated with greater lateral forefoot pressure when walking [5] and standing [6]. Lower arch individuals may have increased pressure under the midfoot [6] or hallux and medial mid-foot [7].…”
Section: Introductionmentioning
confidence: 99%
“…Hegedus et al [8] found that longitudinal arch height does not affect pain. However, high BMI has also been found to influence height of arches [6]. Ankle instability can increase the risk of falls leading to sprains, fractures, and chronic problems.…”
Section: Introductionmentioning
confidence: 99%
“…These include X-rays [10], clinical measurement of navicular drop [11], foot prints and plantar pressure distribution [12,13]. X-rays are accurate; however they are expensive and require attendance at specialized facilities and carry a potential risk of radiation exposure.…”
Section: Arch Structure and The Shoe Type Stabilometermentioning
confidence: 99%